Parental perspectives of prenatal counseling and decision making for termination or hospice birth due to fetal congenital heart defects - Grace Knowles; Diana Madden; Leonardo Barrera; Harshman Sihra; Lynn M. Yee; Jessica T. Fry; William A. Grobman; Natalia Henner; Angira Patel; Sheetal Patel; Joyce L. Woo (PLoS ONE, 2026)
Objective To evaluate perspectives of counseling and decision making among birthing parents who chose termination or hospice birth due to a fetal congenital heart defect (CHD). Methods Qualitative analysis of semi-structured interviews with birthing parents who chose either termination or hospice birth due to severe fetal CHD. Participants were recruited from a purposive sample of those who received multidisciplinary counseling at a tertiary congenital heart surgical center between 2019–2023. Thematic analysis was conducted in five stages, using an integrated deductive-inductive approach. Results In total, 20 individuals were eligible; 10 completed interviews. Identified themes were categorized in two domains: Experiences During Counseling and Individual Factors Affecting Decision Making. Themes in the first domain included: areas for improvement during counseling, perceived strengths of counseling, patient attributes affecting counseling, and views on provider recommendations. Themes in the second domain included: emotions affecting decision making, value for reproductive autonomy, family factors, internal factors, outside input, and desire for resources. Conclusions In this study, birthing parents who chose termination or hospice for fetal CHD appreciated information extending beyond clinical outcomes to include family and financial impacts. Their value for reproductive autonomy reflects the need for clinicians to gain skills in empathetic and neutral counseling of all management options.